2002
DOI: 10.1159/000067898
|View full text |Cite
|
Sign up to set email alerts
|

K<sup>+</sup> Transport and Volume Regulatory Response by NKCC in Resting Rat Hindlimb Skeletal Muscle

Abstract: This study tested the hypothesis that the NKCC is involved in volume regulation, specifically regulatory volume increase (RVI), in resting skeletal muscle. Neurally and vascularly isolated rat hindlimbs were perfused with a bovine erythrocyte perfusate containing 42K or 86Rb as markers of unidirectional K+ flux across the sarcolemma. Compared to controls, perfusion with 120 µM bumetanide (a specific inhibitor of the NKCC) decreased JinK by 15±2%, indicating the funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 46 publications
3
49
0
Order By: Relevance
“…14 The effect of extracellular renin plus Ao on cell volume was due to activation of the Na-K-2Cl cotransporter because bumetanide, an inhibitor of the Na-K-2Cl cotransporter, suppressed the effect of extracellular renin plus Ao on cell volume. The relationship between Na-K-ATPase and Na-K-2Cl contransporter, however, is complex and far from clear 4 and further studies are needed to clarify this relationship, particularly during heart failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 The effect of extracellular renin plus Ao on cell volume was due to activation of the Na-K-2Cl cotransporter because bumetanide, an inhibitor of the Na-K-2Cl cotransporter, suppressed the effect of extracellular renin plus Ao on cell volume. The relationship between Na-K-ATPase and Na-K-2Cl contransporter, however, is complex and far from clear 4 and further studies are needed to clarify this relationship, particularly during heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…3 The relationship between the sodium pump and the cotransporter is complex and not totally clear. 4 In skeletal muscle in culture, for instance, the Na-K-2Cl-mediated K uptake has been found to be insensitive to ouabain, at least during short incubations 5 while in skeletal muscle, in situ, ouabain abolishes the cotransporter. 5 It is known that the circulating renin angiotensin system is an important regulator of blood volume and that intracellular and extracellular renin alters cellular functions like the inward calcium current or gap junctional conductance in the failing heart 6 but no information is available if renin influences heart cell volume.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that one of the important functions of NKCC1 is regulatory volume increase (RVI), which is used to reestablish normal cell volume after cells have been shrunk by exposure to hyperosmotic conditions (9,18,32,37,42). We generated a stable knockdown of WNK3 using shRNAs (WNK3-KD) in D54 glioma cells.…”
Section: Wnk3 Regulation Of Nkcc1 Is Required For Volume Regulation Imentioning
confidence: 99%
“…WNKs have previously been implicated in volume control in tissues tasked with fluid transport such as the kidney (48,49) and epithelium (8). More recently, they have also emerged as important regulators in the brain (7,14,32) where they appear to influence the neuronal Cl Ϫ gradient, which establishes whether the activation of GABA receptors is excitatory or inhibitory. More importantly, the WNKs have been implicated in Cl Ϫ flux in various cells types and are able to phosphorylate and regulate SPAK, OSR1, and other WNK family members (1,12,28,29,48).…”
Section: Disscussionmentioning
confidence: 99%
“…The only viable explanation for a simultaneous decrease in ECFV and increase in ICFV during this period of exercise recovery is an increase in intracellular osmolality and/or decrease in extracellular osmolality. While the mechanism(s) responsible for these responses remain(s) to be determined, they may be attributed to an increase in metabolic and ionic osmolytes (glycogen, potassium) within recovering skeletal muscle, to an increase in cellular Na þ -K þ -2Cl 2 co-transporter activity in order to restore volume of non-contracting tissues 29 , and to an increase in cellular Na þ -K þ -2Cl 2 co-transporter activity in order to restore intracellular [K þ ] of recovering skeletal muscle 9,30 .…”
Section: Recovery From Exercisementioning
confidence: 99%